Specific humoral immunity versus polyclonal B cell activation in Trypanosoma cruzi infection of susceptible and resistant mice. - Marianne A Bryan; Siobhan E Guyach; Karen A Norris (Public Library of Science (PLoS), 2010)
The etiologic agent of Chagas Disease is Trypanosoma cruzi. Acute infection results in patent parasitemia and polyclonal lymphocyte activation. Polyclonal B cell activation associated with hypergammaglobulinemia and delayed specific humoral immunity has been reported during T. cruzi infection in experimental mouse models. Based on preliminary data from our laboratory we hypothesized that variances in susceptibility to T. cruzi infections in murine strains is related to differences in the ability to mount parasite-specific humoral responses rather than polyclonal B cell activation during acute infection.Relatively susceptible Balb/c and resistant C57Bl/6 mice were inoculated with doses of parasite that led to similar timing and magnitude of initial parasitemia. Longitudinal analysis of parasite-specific and total circulating antibody levels during acute infection demonstrated that C57Bl/6 mice developed parasite-specific antibody responses by 2 weeks post-infection with little evidence of polyclonal B cell activation. The humoral response in C57Bl/6 mice was associated with differential activation of B cells and expansion of splenic CD21(high)CD23(low) Marginal Zone (MZ) like B cells that coincided with parasite-specific antibody secreting cell (ASC) development in the spleen. In contrast, susceptible Balb/c mice demonstrated early activation of B cells and early expansion of MZ B cells that preceded high levels of ASC without apparent parasite-specific ASC formation. Cytokine analysis demonstrated that the specific humoral response in the resistant C57Bl/6 mice was associated with early T-cell helper type 1 (Th1) cytokine response, whereas polyclonal B cell activation in the susceptible Balb/c mice was associated with sustained Th2 responses and delayed Th1 cytokine production. The effect of Th cell bias was further demonstrated by differential total and parasite-specific antibody isotype responses in susceptible versus resistant mice. T cell activation and expansion were associated with parasite-specific humoral responses in the resistant C57Bl/6 mice.The results of this study indicate that resistant C57Bl/6 mice had improved parasite-specific humoral responses that were associated with decreased polyclonal B cell activation. In general, Th2 cytokine responses are associated with improved antibody response. But in the context of parasite infection, this study shows that Th2 cytokine responses were associated with amplified polyclonal B cell activation and diminished specific humoral immunity. These results demonstrate that polyclonal B cell activation during acute experimental Chagas disease is not a generalized response and suggest that the nature of humoral immunity during T. cruzi infection contributes to host susceptibility.